Designing a Self Assessment Tool in the Framework of Preparing Halal Assurance and Food Safety in Ant Sugar Production in UP2K Fifty City Regency - Desriyenti Desriyenti Desriyenti; Nilda Tri Putri; Alexie Herryandie Bronto Adi (Riwayat: Educational Journal of History and Humanities, 2023)
The Indonesian government has a responsibility for every product that is marketed to be guaranteed safety with evidence from BPOM and has a halal label in accordance with laws and regulations regarding halal assurance. Ant sugar is a powder-shaped sugar derived from fresh nira water and the production process is still the same as palm sugar production. The production process of this sugar is still manual so that it is easily contaminated both chemical, physical and biological contamination and its halal guarantee system. The purpose of the research is to identify important elements and sources of physical, chemical, biological and halal hazards in the ant sugar production process activities using the HACCP method which refers to ISO 22000: 2018 while the halal assurance system refers to HAS 23000. The method used is qualitative descriptive method. This study can be concluded that there are physical hazards in the ant sugar production process activities such as hair, dust, sand, leaves. Chemical hazards in the form of heavy metal contamination, detergents and temperature. While biological hazards in the form of bacteria, and khamr. These hazards occur in the ant sugar production process activities in the process of tapping sap water, cooking/evaporation process. While in terms of haram / unclean at the time of tapping sap water, the fermentation process occurs. The design of this check sheet is designed based on the verification results of the control flowchart which aims to see the flow of the palm sugar production process and minimize the occurrence of hazard contamination